SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fluids on Injection Strategies to Suppress Pre-Ignition

Abstract: Pre-ignition is an abnormal engine combustion phenomenon where the inducted fuel-air charge ignites before the spark ignition. This premature combustion phenomenon often leads to heavy knocking events. The mixture preparation plays a critical role in pre-ignition tendency for a given load. Literature shows efforts made towards improving pre-ignition-limited-IMEP by splitting the injection pulse into multiple pulses. In this study, two direct injectors are used in a single cylinder research engine. A centrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In previous work, we direct-injected water late in the exhaust stroke to cool/quench only the residual exhaust without impacting the fresh incoming mixture (by finishing water injection before intake valve opening time) [23,24]. Such strategy significantly suppressed preignition frequency, supporting the idea that reactive debris in the residual gas is the cause for triggering pre-ignition in the subsequent cycle.…”
Section: Results and Discussion: Exploration #1: Pre-ignition Prediction From Exhaust Cycle Ion Signal And Mitigation Strategymentioning
confidence: 61%
“…In previous work, we direct-injected water late in the exhaust stroke to cool/quench only the residual exhaust without impacting the fresh incoming mixture (by finishing water injection before intake valve opening time) [23,24]. Such strategy significantly suppressed preignition frequency, supporting the idea that reactive debris in the residual gas is the cause for triggering pre-ignition in the subsequent cycle.…”
Section: Results and Discussion: Exploration #1: Pre-ignition Prediction From Exhaust Cycle Ion Signal And Mitigation Strategymentioning
confidence: 61%
“…Water injection has been explored further, concerning its preignition suppression tendency in a previous work . Key findings relevant to the preignition suppression by water injection are discussed here.…”
Section: Resultsmentioning
confidence: 97%
“…Water injection at −50 CAD aTDC was not effective beyond intake air pressure 1.07 bar case. Previously, the authors have observed that injecting water very close to the top dead center may not allow the best charge cooling because of incomplete evaporation by the time of spark . Representative data for only two cases: intake air pressure of 1.60 and 1.80 bar are shown in the results below.…”
Section: Resultsmentioning
confidence: 99%
“…It also appears to confirm the link between the previous cycle and pre-ignition event, which has been the subject of some debate within the research community. More details on the experiment are part of [36].…”
Section: Effect Of Injecting Water Late In the Exhaust Strokementioning
confidence: 99%